Beyond Recidivism: A Systematic Review Exploring Comprehensive Criteria for Successful Reintegration After Prison Release - Mourão, Ana (Criminal justice and behavior, 2025)
Individuals who have served prison sentences face challenges in reintegrating into society, with recidivism often used as the primary indicator of reintegration success. This systematic review analyzed 38 studies with adult participants who had served a sentence or were in the last year of prison, identifying criteria for successful reintegration after release and risk and protective factors. Success factors cover intrapersonal (health, drug abstinence), interpersonal (social support, community involvement), institutional (institutional and community support), and community domains (employment and housing). Protective factors include emotional stability, family and community support, education, employment, financial stability, and access to health and social services. Risk factors include drug use, health problems, difficulties with family and social adjustment, job and financial instability, low education, housing instability, and discrimination. The findings underscore that reintegration is a complex and multifaceted process, requiring targeted programs to reduce recidivism and stigma and promote effective reintegration into society.